A multiaxial inertial macroelement for deep foundations. (March 2023) - Gorini, Davide Noè; Callisto, Luigi
Abstract: A hyperplastic macroelement is proposed as an efficient means for simulating nonlinear and multi-directional soil-piles interaction in the nonlinear analysis of structures. The macroelement relates the generalised forces exchanged between the superstructure and the foundation to the corresponding displacements and rotations of the foundation raft. The inertial effects developing under dynamic loading can be reproduced by coupling the macroelement with the participating masses of the soil-foundation system, obtainable with a modal identification of the pile group. Failure conditions of the foundation are described by a hyper-ovoidal ultimate limit state surface in the force space, which is calibrated through standardised procedures. The plastic behaviour, controlled by a series of yield surfaces with kinematic hardening, produces the desired directional coupling and allows to model the cyclic response and the irreversible deformation of the foundation. The macroelement is implemented in the analysis framework OpenSees for a prompt use in earthquake engineering applications. Its predictions under monotonic loads are validated against experimental data and advanced, fully coupled numerical modelling, while its dynamic response is tested on a reference case study.